FEATURES OF A STATE OF HEALTH AND FUNCTIONING SYSTEMS OF AN ORGANISM OF YOUNGER SCHOOLBOYS DEPENDING ON SOCIAL-PSYCHOLOGICAL ADAPTATION TO TRAINING AT SCHOOL - Danilenko, G.N.; Popov, N.N.; Pashkevich, S.A.; YabluchanskyА.N. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine")
Features of formation of health, functioning of immune system of younger schoolboys are defined depending on a degree of adaptation to conditions of education.